2013
DOI: 10.1371/journal.pone.0075963
|View full text |Cite|
|
Sign up to set email alerts
|

Progressive Retinal Degeneration and Glial Activation in the CLN6nclf Mouse Model of Neuronal Ceroid Lipofuscinosis: A Beneficial Effect of DHA and Curcumin Supplementation

Abstract: Neuronal ceroid lipofuscinosis (NCL) is a group of neurodegenerative lysosomal storage disorders characterized by vision loss, mental and motor deficits, and spontaneous seizures. Neuropathological analyses of autopsy material from NCL patients and animal models revealed brain atrophy closely associated with glial activity. Earlier reports also noticed loss of retinal cells and reactive gliosis in some forms of NCL. To study this phenomenon in detail, we analyzed the ocular phenotype of CLN6nclf mice, an estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 41 publications
1
56
0
1
Order By: Relevance
“…Moreover, intake of docosahexaenoic acid also improved the retinal morphology by preservation of the photoreceptor layer thickness. 59 Our hypothesis that nonsyndromic retinal degeneration is caused by relatively mild MFSD8 deficiencies could imply that only a minor increase of protein function, or suppression of Müller cell activation, might result in a significant therapeutic effect.…”
Section: Discussionmentioning
confidence: 87%
“…Moreover, intake of docosahexaenoic acid also improved the retinal morphology by preservation of the photoreceptor layer thickness. 59 Our hypothesis that nonsyndromic retinal degeneration is caused by relatively mild MFSD8 deficiencies could imply that only a minor increase of protein function, or suppression of Müller cell activation, might result in a significant therapeutic effect.…”
Section: Discussionmentioning
confidence: 87%
“…Longer-term studies will be needed to investigate the safety and effectiveness of these approaches. Other proposed treatments, including substrate reduction and use of anti-inflammatory reagents, can contribute to mitigating aspects of MPS pathology [12,52,71]. Because of its exceptionally good toxicological profile [72,73], trehalose might be safely used in combination therapies to investigate its additive or synergistic effects with other therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…Turmeric is a household staple in India, with reported average daily consumption ranging from 0.24 g/person/day to as high as 4g/person/day [80, 81]. Curcumin, which is a naturally polyphenolic compound found in turmeric has multifaceted medicinal properties and has been implicated in helping to treat several types of neurological disorders including Alzheimer’s disease [39, 82, 83], retinal diseases [84, 85], Parkinson’s disease [86, 87], stroke [88], brain injury [22, 41, 42] and psychiatric disorders [89–91]. We recently reported that curcumin supplementation promoted increased DHA content in the brain following TBI, and that this effect was associated with elevated levels of enzymes involved in DHA synthesis [22].…”
Section: Discussionmentioning
confidence: 99%